The Ethnomathematics of Symmetric War-boat of Biak Tribe - Sroyer, Alvian M.; Nainggolan, Jonner; Beno, Ishak S.; Reba, Felix (Universitas Papua, 2025)
The Wairon is a traditional warboat of the Biak tribe, characterized by its unique symmetrical structure tailored for combat navigation. This research explores the mathematical principles embedded in its construction from an ethnomathematical perspective, addressing the gap in literature on how indigenous maritime engineering reflects advanced spatial reasoning. The study aims to document and analyze the symmetrical design elements of the Wairon to uncover how Biak boatbuilders apply geometric and anthropometric logic in practice. Using an exploratory qualitative method with triangulation, data were gathered through 12 in-depth interviews with cultural experts and elder artisans, direct observations of three traditional boat-building sessions, and literature analysis of maritime knowledge. Triangulation was applied by comparing themes that emerged independently across these three data sources. The collected qualitative data were analyzed using a thematic coding framework with multiple coding cycles, focusing on patterns of symmetry, measurement techniques, and structural logic. Codes were reviewed through peer validation and saturation was reached after the third data source. Symmetry in this study is operationally defined as bilateral congruence across a central longitudinal axis, as observed in the mirrored placement of najun (crossbeams), outriggers, pegs, and bow carvings. Evidence was gathered through measurements of spatial repetition, alignment consistency, and anthropometric mapping (e.g., arm span and fathom units) used by artisans during construction. Key findings highlight that the Wairon's design reflects a high degree of symmetry not only for aesthetic or symbolic purposes but also for tactical advantages in battle, allowing seamless directional shifts. The theoretical implications contribute to the expansion of ethnomathematics by contextualizing symmetry as both a cultural logic and a navigational solution, while practically, these insights provide a model for integrating indigenous design principles into STEM education and support initiatives for digital heritage preservation and virtual reconstruction of traditional technologies